Study on rainfall infiltration characteristic parameters of unsaturated soil - Zhong, Lijia; Wang, Bo; Zhao, Xuguang; Liu, Fengyin; Miao, Meng; Pu, Cheng (Frontiers in Ecology and Evolution, 2023)
The study of the rainfall infiltration mechanism of unsaturated soil has always been a hot issue in the field of geotechnical engineering. It is worth studying which parameters should be introduced to characterize the infiltration characteristics of unsaturated soil in the calculation and analysis of rainfall infiltration. In this paper, the Fredlund–Xing model was quoted in the SEEP/W module of the Geostudio software, and the transient numerical calculation of rainfall infiltration under the same rainfall duration T and different rainfall intensity I was carried out for a soil column. Three infiltration characteristic parameters were introduced: rainfall infiltration front depth WF, suction reduction depth MRn, and section infiltration rate IR. The variation of these three parameters and rainfall intensity I during rainfall were sorted out and analyzed; it is indicated that WF increases with the extension of rainfall duration. MRn decreases with the increase of suction reduction rate n%, and when the rainfall duration is 24 h, the maximum depth of the soil column affected by rainfall is approximately 35% of the total depth. IR is mainly affected by the rainfall intensity I and the saturation permeability coefficient ks. There is a limit value for the influence of I on WF, MRn, and IR, and the limit rainfall intensity under the calculation conditions in this paper is I = 2.5ks.